MANAGEMENT OF A PILOT TAHFIDZ CLASS PROGRAM IN ENHANCING THE QUALITY OF ISLAMIC EDUCATION AT MI MA’ARIF WRINGINPUTIH - Maiyakhwa Zakia Amalia; Abdul Aziz (Jurnal Manajemen Pendidikan, 2026)
The Qur'anic memorization (tahfidz) program has increasingly emerged as a strategic initiative for improving the quality of Islamic education in madrasahs. However, programs that are still in their developmental stage often encounter various managerial challenges, limiting the effectiveness of their implementation. This study aims to analyze the implementation of management functions in managing a pilot tahfidz class, identify the supporting and inhibiting factors, and examine its contribution to improving the quality of Islamic education at MI Ma'arif Wringinputih. This study employed a qualitative approach using a case study design. Data were collected through interviews, observations, and document analysis involving the madrasah principal, the tahfidz instructor, the homeroom teacher, students, and parents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that the program has implemented the four management functions—planning, organizing, actuating, and controlling—although planning, the formulation of performance indicators, and the evaluation system still require further improvement. The program's success is supported by collaboration among the principal, teachers, the foundation, students, and parents, while the shortage of dedicated tahfidz teachers, the scheduling of activities after regular classroom instruction, and students' diverse learning abilities remain the primary challenges